2021
DOI: 10.1016/j.clnesp.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A hypocaloric diet rich in high fiber rye foods causes greater reduction in body weight and body fat than a diet rich in refined wheat: A parallel randomized controlled trial in adults with overweight and obesity (the RyeWeight study)

Abstract: Background and aim: A high intake of whole grain foods is inversely associated with body mass index (BMI) and body fat in observational studies, but mixed results have been found in interventional studies. Among whole grains, rye is the richest source of dietary fiber and meals containing high-fiber rye foods have shown increased satiety up to 8 h, compared to meals containing refined wheat products. The aim of the study was to determine the effect of consuming high fiber rye products, compared to refined whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Consumption of whole grains in preference to refined grains is known to have improved health benefits, with the broad range of benefits often attributed solely to the presence of dietary fiber [10,53]; however, other components, phytochemicals, fatty acids, amino acids, vitamins, and minerals are all likely to play a role. This review of 31 RCTs found that consumption of whole grain foods had a moderate effect on reducing inflammatory markers, with five of the possible 15 crossover studies [33,38,40,42,50], and seven of 16 parallel studies demonstrating statistically significant changes [23,[29][30][31][32]43,49]. Within the population groups studied, the reduction in markers was most often observed in obese and overweight populations, and among those with pre-existing conditions, compared with studies of healthy populations, although there were only two studies in this category.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consumption of whole grains in preference to refined grains is known to have improved health benefits, with the broad range of benefits often attributed solely to the presence of dietary fiber [10,53]; however, other components, phytochemicals, fatty acids, amino acids, vitamins, and minerals are all likely to play a role. This review of 31 RCTs found that consumption of whole grain foods had a moderate effect on reducing inflammatory markers, with five of the possible 15 crossover studies [33,38,40,42,50], and seven of 16 parallel studies demonstrating statistically significant changes [23,[29][30][31][32]43,49]. Within the population groups studied, the reduction in markers was most often observed in obese and overweight populations, and among those with pre-existing conditions, compared with studies of healthy populations, although there were only two studies in this category.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews and meta analyses, performed by Rahmani et al [17] and Hajihashemi et al [18] utilising publications up until 2019, found little evidence of a relationship between whole grain consumption and inflammatory markers. The current review included a total of 13 papers not included in the aforementioned reviews [17,18], six of which were published outside the timeframe utilized by the previous authors [30,31,41,43,44,52], and a further seven were included in the current review due to a variation in the search strategy [23,29,37,39,42,45,51].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations